2016
DOI: 10.1037/xan0000114
|View full text |Cite
|
Sign up to set email alerts
|

Testing the boundaries of “paradoxical” predictions: Pigeons do disregard bad news.

Abstract: Several studies have shown that, when offered a choice between an option followed by stimuli indicating whether or not reward is forthcoming and an option followed by noninformative stimuli, animals strongly prefer the former even when the latter is more profitable. Though this paradoxical preference appears to question the principles of optimal foraging theory, Vasconcelos, Monteiro, and Kacelnik (2015) proposed an optimality model that shows how such preference maximizes gains under certain conditions. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
71
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 33 publications
4
71
2
Order By: Relevance
“…However, if the signaled-win functioned as good news that encouraged responding for the risky option, then it is reasonable that a signaled-loss would function as bad news that would discourage responding on the risky option and cancel out the effects of the good news, or worse have an overall impact of discouraging responding on the risky option because a signaled-loss was encountered more frequently. However, the loss-signal appears to play no significant role in affecting choices (Fortes et al, 2016; Laude et al, 2014; Vasconcelos et al, 2015). In the present study the signaled-loss outcome was more likely to be followed with continued selections of the risky option rather than with a switch to the safe option, demonstrating that the monkeys were insensitive to the signaled losses.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, if the signaled-win functioned as good news that encouraged responding for the risky option, then it is reasonable that a signaled-loss would function as bad news that would discourage responding on the risky option and cancel out the effects of the good news, or worse have an overall impact of discouraging responding on the risky option because a signaled-loss was encountered more frequently. However, the loss-signal appears to play no significant role in affecting choices (Fortes et al, 2016; Laude et al, 2014; Vasconcelos et al, 2015). In the present study the signaled-loss outcome was more likely to be followed with continued selections of the risky option rather than with a switch to the safe option, demonstrating that the monkeys were insensitive to the signaled losses.…”
Section: Discussionmentioning
confidence: 98%
“…This includes evidence that delaying the win signals fails to encourage risky choices (McDevitt et al, 1997; Vasconcelos, et al, 2015) and evidence that selectively enhancing the magnitude of a signaled risky-loss does not disrupt the control that the signaled-win maintains over encouraging risky choices (Fortes, Vasconcelos, & Machado, 2016). Laude, Stagner, and Zentall (2014) explored this issue by replicating the Zentall and Stagner (2011) procedure with pigeons choosing between a 3-pellet safe option and a 10-pellet (at 0.2 probability) risky option.…”
mentioning
confidence: 99%
“…While there has been a recent wave of articles published on suboptimal choice (for reviews, see McDevitt et al, 2016;Vasconcelos et al, 2018;and Zentall, 2016), most of the focus has been placed on the role of the terminal links in determining preference (e.g., Fortes, Pinto, Machado, & Vasconcelos, 2018;Fortes, Vasconcelos, & Machado, 2016;McDevitt, Pisklak, Spetch, & Dunn, 2018;Pisklak et al, 2015;Stagner et al, 2012;Stagner & Zentall, 2010). In most studies of suboptimal choice the initial-link schedule is an FR 1.…”
mentioning
confidence: 99%
“…Animals are expected to disengage from stimuli that signal the absence of food and, as a result, the probability of receiving these stimuli does not affect choice. Consistent with these predictions, studies with starlings (Vasconcelos Monteiro, & Kacelnik, ) and pigeons (Fortes et al, ) have found that preference for a signaled alternative over a more optimal unsignaled alternative remains strong despite decreases in reward probability on the signaled alternative, and this suboptimal preference decreases only at very low probabilities (e.g. < 0.1).…”
mentioning
confidence: 74%
“…Another recent model, based on considerations of foraging behavior in the natural environment, similarly predicts that reinforcement frequency on a signaled alternative should have no effect on preference (Fortes, Machado, & Vasconcelos, 2017;Fortes, Pinto, Machado, & Vasconcelos, 2018;Fortes, Vasconcelos, & Machado, 2016;Vasconcelos, Machado, & Pandeirada, 2018). One formalization of this functional model, called the reinforcement rate model (RRM) focuses on the rate of energy intake in the presence of informative (i.e., signaled) stimuli and noninformative (unsignaled) stimuli (Fortes et al, 2017).…”
mentioning
confidence: 99%